Eksperimen Pembelajaran Matematika Dengan Strategi College Ball Dan Quiz Team Terhadap Hasil Belajar Ditinjau Dari Kemampuan Komunikasi Pada Siswa Kelas Viii Smp Negeri 1 Ngemplak Tahun 2015/2016 - Septiyani, Dwi (2016)
The aim of research to describe and analyze: (1) the influence of mathematics learning with College Ball and Quiz Team berdasrkan result of learning mathematics, (2) the effect of communication skills to the learning outcomes of mathematics, (3) the interaction between the learning strategies and communication skills to the learning outcomes mathematics. This research is a quasi experimental with experimental design. The study population was all class VIII SMP N 1 Ngemplak grade second semester of the 2015/2016 academic year. The study sample consisted of two classes. The sampling technique using cluster random sampling. The test method usage data collection and documentation. Data were analyzed by analysis of variance with two different cell lines. The results of the data analysis with a significance level of 5% was obtained: (1) there is the influence of College Ball and Quiz Team on learning outcomes of mathematics, with FA = 6,487 (2) No effect of communication skills for learning outcomes mathematics, with FB = 57,156 (3) there is no interaction between College Ball and Quiz Team the communication skills with the learning outcomes, with FAB = 1,591.